25) \( 15^{-6 p-6}-6.2=62 \)
Solución de tutoría real
Responder
Solución
Revisado y aprobado por el equipo de tutoría de UpStudy
Mind Expander
To solve the equation \( 15^{-6p-6} - 6.2 = 62 \), we first isolate the term involving the exponent. Adding \( 6.2 \) to both sides gives: \[ 15^{-6p-6} = 62 + 6.2 = 68.2 \] Now we can take the logarithm of both sides. Using base 10 or natural logarithm is fine, but we'll use base 10 for clarity: \[ \log(15^{-6p-6}) = \log(68.2) \] Using the power rule of logarithms: \[ (-6p - 6) \log(15) = \log(68.2) \] Now, we can solve for \( p \): \[ -6p - 6 = \frac{\log(68.2)}{\log(15)} \] Now, distributing the negative sign gives us: \[ 6p + 6 = -\frac{\log(68.2)}{\log(15)} \] Dividing every term by 6: \[ p + 1 = -\frac{\log(68.2)}{6\log(15)} \] Subtracting 1: \[ p = -\frac{\log(68.2)}{6\log(15)} - 1 \] Thus, the final simplified expression for \( p \) is: \[ p = -\frac{\log(68.2)}{6\log(15)} - 1 \] Feel free to compute the values for \( \log(68.2) \) and \( \log(15) \) to find a numerical solution for \( p \).